(untitled) (Acta Entomologica Serbica, 2020)
This paper examines the effects of different light spectra on the number of eggs of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) as a general host of biological control agents. Six distinct spectra of light, ranging from 395 nm to 625 nm, were examined in laboratory conditions. Green and red spectra with ranges of 520-525 nm and 620-625 nm caused the highest and the lowest numbers of eggs, respectively. Additionally, the effects of time on the mean egg load of E. kuehniella were also found to be significant at five days. The implications of the current results are discussed below and suggest that the application of a green spectrum in insectariums could help in increasing egg production.